A low-temperature-printed hierarchical porous sponge-like scaffold that promotes cell-material interaction and modulates paracrine activity of MSCs for vascularized bone regeneration. (July 2021) - Lian, Meifei; Sun, Binbin; Han, Yu; Yu, Bin; Xin, Weiwei; Xu, Ruida; Ni, Bing; Jiang, Wenbo; Hao, Yongqiang; Zhang, Xiuyin; Shen, Yi; Qiao, Zhiguang; et al.
Abstract: Mesenchymal stem cells (MSCs) secrete paracrine trophic factors that are beneficial for tissue regeneration. In this study, a sponge-like scaffold with hierarchical and interconnected pores was developed using low-temperature deposition modeling (LDM) printing. Its effects on the cellular behavior, especially on the paracrine secretion patterns of MSCs, were comprehensively investigated. We found that compared with the scaffolds printed via the fused deposition modeling (FDM) technique, the LDM-printed sponges enhanced the adhesion, retention, survival, and ingrowth of MSCs and promoted cell-material interactions. Moreover, the paracrine functions of the cultured MSCs on the LDM-printed sponges were improved, with significant secretion of upregulated immunomodulatory, angiogenic, and osteogenic factors. MSCs on the LDM-printed sponges exert beneficial paracrine effects on multiple regenerative processes, including macrophage polarization, tube formation, and osteogenesis, verifying the enhanced immunomodulatory, angiogenic, and osteogenic potential. Further protein function assays indicated that focal adhesion kinase (FAK), downstream AKT, and yes-associated-protein (YAP) signaling might participate in the required mechanotransductive pathways, through which the hierarchical porous structures stimulated the paracrine effects of MSCs. In a rat distal femoral defect model, the MSC-laden LDM-printed sponges significantly promoted vascularized bone regeneration. The results of the present study demonstrate that the hierarchical porous biomimetic sponges prepared via LDM printing have potential applications in tissue engineering based on their cell-material interaction promotion and MSC paracrine function modulation effects. Furthermore, our findings suggest that the optimization of biomaterial properties to direct the paracrine signaling of MSCs would enhance tissue regeneration.